Viabilidade de manutenção do teletrabalho em uma Instituição Federal de Ensino Superior no contexto pós-pandemia de Covid-19 - Enio de Paula Fernandes (2021)
This study sought to identify, from the point of view of managers of the Federal University of Mato Grosso do Sul (UFMS), the feasibility of maintaining telework at this University. Telework was implemented at UFMS in an emergency way due to the declaration by the World Labor Organization of a pandemic scenario resulting from the contamination of the coronavirus called COVID-19, which originated in 2019 in China and spread around the world. Given this context, UFMS defined coping measures for the situation, from adapting administrative routines to remote teaching, through information and communication technology. Considering this enormous challenge of implementing the work modality in the context of education, which is mostly done face-to-face, this research was developed with the documental analysis of information obtained in the UFMS central administration units and by means of interviews with the managers of central, sectorial and campus units of the State. Through qualitative analysis, it was observed that the interviewees understand that the maintenance of telework is feasible, but there were different understandings as to the feasibility of maintenance because of the specificities that higher education presents in various areas, and there are still those who believe that a hybrid model of work is possible. Based on this study, a model of a management program is presented to the central administration of UFMS in which it is possible to maintain telework for technical-administrative servers, with the selection of professionals able to perform this kind of work with the fulfillment of the established goals. It is intended, thus, to contribute to the advancement of work processes and at the same time contribute to a modernization of public service.